Aderência de revestimentos em paredes de blocos cerâmicos com função estrutural - Camacho, Jefferson Sidney (2016)
Abstract The aim of this paper is to assess the mechanical behaviour of ceramic tiles on a structural masonry wall submitted to vertical loading. This study presents the results and conclusions of experiments carried out on ceramic block masonry walls coated with ceramic tiles and submitted to increasing vertical loads up to the system's complete failure. The ceramic tiling was applied on the walls using dry set mortars either directly on the blocks or on a plastering mortar layer. During the tests, all the important events, such as strains, onset cracks, tile detaching, rupture shape and load values, were registered. It was possible to determine the relationship between loads and the occurrence of cracks or tile detachment. Cracking or detachment of ceramic tiles only occurred at load values close to each wall's failure load. That indicates that the tiles had good adherence to the wall up to loads much higher than those expected. This indicates that the rendering tyles did not have any visual or mechanical failures when they were on walls under service loads